Prurigiform Angiomatosis: Reactive Angioproliferation in the Skin and Vascular Endothelial Growth Factors. (January 2020) - Ortins-Pina, Ana; Soares-de-Almeida, Luís; Caroli, Ulrich; Held, Laura; Kempter, Wolfgang; Rütten, Arno; Mentzel, Thomas; Kutzner, Heinz
Abstract : Background: Cutaneous benign angioproliferations can be diagnostically challenging and may mimic vascular tumors. Keratinocytes express vascular endothelial growth factors (VEGFs). We studied the angiogenic factor expression pattern in cutaneous lesions with a distinctive pattern of remarkable dermal angiomatosis underlying prurigo-like epidermal changes. Methods: Cases were selected retrospectively from 2012 to 2018, and their VEGF staining pattern was compared with normal skin and other reactive skin conditions. Results: Thirty-eight patients, median age 76 years, mostly men (74%), presented with asymptomatic patches or plaques, most commonly located on the buttocks (n = 17) and/or intergluteal fold (n = 12), often eliciting concern for neoplasia (n = 19). Microscopically, all cases featured a prominent proliferation of dilated capillaries and postcapillary venules, underneath epidermal changes resembling prurigo or lichen simplex chronicus. In one-third, a subepidermal lymphocytic infiltrate was present. Immunostaining with VEGF was positive in the upper 4/5 of the epidermis overlying the angioproliferation, in contrast with nonlesional skin, where VEGF positivity was limited to the stratum granulosum. Receptor VEGFR-2 was expressed in the endothelia of neovessels. Conclusions: We propose the term prurigiform angiomatosis for the morphological picture of prurigo/lichen simplex chronicus-like epidermal hyperplasia with prominent dermal angioproliferation. Mechanical injury and inflammation are the likely triggers of this reactive angiogenesis pattern, driven by epidermal VEGF expression.